PACK Child: the development of a practical guide to extend the scope of integrated primary care for children and young adolescents. (23rd October 2018) - Picken, Sandy; Hannington, Juliet; Fairall, Lara; Doherty, Tanya; Bateman, Eric; Richards, Mark; Wattrus, Camilla; Cornick, Ruth
Abstract : Pioneering strategies like WHO's Integrated Management of Childhood Illness (IMCI) have resulted in substantial progress in addressing infant and child mortality. However, large inequalities exist in access to and the quality of care provided in different regions of the world. In many low-income and middle-income countries, childhood mortality remains a major concern, and the needs of children present a large burden upon primary care services. The capacity of services and quality of care offered require greater support to address these needs and extend integrated curative and preventive care, specifically, for the well child, the child with a long-term health need and the child older than 5 years, not currently included in IMCI. In response to these needs, we have developed an innovative method, based on experience with a similar approach in adults, that expands the scope and reach of integrated management and training programmes for paediatric primary care. This paper describes the development and key features of the PACK Child clinical decision support tool for the care of children up to 13 years, and lessons learnt during its development.